Prevalence and reasons for intentional use of complementary and alternative medicine as an adjunct to future visits to a medical doctor for chronic disease - Agnete E. Kristoffersen; Trine Stub; Frauke Musial; Vinjar Fønnebø; Ola Lillenes; Arne Johan Norheim (BMC, 2018)
Abstract Background Intentional use of complementary and alternative medicine (CAM) has previously only been researched in small, possibly biased, samples. There seems to be a lack of scientific information regarding healthy individual's attitudes and presumed use of CAM. The aim of this study is to describe prevalence and characteristics of participants who intend to see a CAM provider compared to participants who intend to see a medical doctor (MD) only when suffering from a chronic, non- life-threatening disease and in the need of treatment. Further to describe differences between the groups regarding expected reasons for CAM use and expected skills of CAM providers. Method The survey was conducted in January 2016 as part of the "TNS Gallup Health policy Barometer". In total, 1728 individuals aged 16-92 years participated in the study, constituting an overall response rate of 47%. The survey included questions regarding opinions and attitudes towards health, health services and health politics in Norway. Results The majority of the participants (90.2%) would see a MD only if they were suffering from a chronic, non- life-threatening disease and were in the need of treatment. Men over the age of 60 with a university education tended to see a MD only. Only 9.8% of all respondents would in addition visit a CAM provider. Being an intentional user of a MD + CAM provider was associated with being a woman under the age of 60. The respondents believed that CAM providers have professional competence based on formal training in CAM. They also believed that individuals seeing a CAM provider have poor health and are driven by the hope of being cured. Further, that they have heard that others have good experience with such treatment. Conclusion Intentional use of CAM is associated with positive attitudes, trustworthiness, and presumed positive experiences in the CAM-patient-setting. Intentional CAM users also have the impression that CAM providers have professional competence based on formal training in alternative therapies.